Sensor node placement based on lexicographic minimax - Abidin H.Z.; Din N.Md. (2023)
Wireless Sensor Networks (WSN) which is capable in sensing, storing, processing and transmitting data has been widely applied in providing effective surveillance. Optimum sensor nodes placement in the surveillance area is needed to optimise the cost and efficiency of deployment. The positions of sensor nodes should be able to provide maximum coverage with longer lifetime. This paper proposed a sensor nodes placement technique which is based on the lexicographic minimax algorithm. Performance study has been carried out by comparing the performance of the lexicographic minimax sensor node placement scheme with traditional minimax technique in terms of coverage ratio and uniformity. Uniformity is a performance metric that can be used to estimate WSN lifetime. Simulation results show that the WSN deployed with lexicographic minimax sensor node placement scheme outperforms minimax scheme with larger coverage ratio and is expected to provide longer lifetime. 2012 IEEE.